The politics of higher education : the Imperial University in Northern Song China - Chu, Ming-kin (Hong Kong University Press, 2020)
The Politics of Higher Education: The Imperial University in Northern Song China uses the history of the Imperial University of the Northern Song to show the limits of the Song emperors' powers. At the time, the university played an increasingly dominant role in selecting government officials. This role somehow curtailed the authority of the Song emperors, who did not possess absolute power and, more often than not, found their actions to be constrained by the institution. The nomination mechanism left room for political maneuvering and stakeholders--from emperors to scholar-officials--tried to influence the process. Hence, power struggles among successive emperors trying to assert their imperial authority ensued. Demands for greater autonomy by officials were, for example, unceasing. Chu Ming-kin shows that the road to autocracy was anything but linear. In fact, during the Northern Song dynasty, competition and compromises over diverse agendas constantly altered the political landscape.